The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3342/ceo.2015.8.2.97
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Oxidative Stress in the Serum and Tissue Specimens of Patients With Chronic Otitis Media

Abstract: ObjectivesTo underline the effect of oxidative stress in chronic otitis media with and without cholesteatoma and to compare the oxidative stress values in the serum and tissue specimens in these two forms.MethodsThe study included a total of 75 individuals, 35 cases with chronic otitis media (COM; 16 females and 19 males) and a healthy control group of 40 cases (20 females and 20 males). The COM patient group was comprised of 18 patients with cholesteatoma and 17 patients without cholesteatoma. All patients un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…In our study, the MDA levels in the patients group with CSOM with and without cholesteatoma and cholesteatoma recidivism were higher compared to the healthy group, which reflect an increased lipid peroxidation, a result similar to a 2015 study [22]. According to Holecek et al,lipoperoxidation may be a marker of disease severity in otitis media,being involved in many other otorhinolaryngological diseases [23][24][25].…”
Section: Resultssupporting
confidence: 76%
“…In our study, the MDA levels in the patients group with CSOM with and without cholesteatoma and cholesteatoma recidivism were higher compared to the healthy group, which reflect an increased lipid peroxidation, a result similar to a 2015 study [22]. According to Holecek et al,lipoperoxidation may be a marker of disease severity in otitis media,being involved in many other otorhinolaryngological diseases [23][24][25].…”
Section: Resultssupporting
confidence: 76%
“…Previously, Garca et al found significantly elevated serum and tissue sample levels of malondialdehyde which was a marker of lipid peroxidation and decreased levels of antioxidant enzymes like superoxide dismutase, catalase and glutathione peroxidase. [20] To the best of our knowledge, this is the first study that investigated thiol/disulphide homeostasis as a novel marker of oxidative stress in patients with COM and compared the results with healthy controls.…”
Section: Discussionmentioning
confidence: 98%
“…This persistent inflammatory stimulation causes pathologic changes in the tissues and inhibits healthy tissue recovery. Moreover, oxidative stress can damage ciliary structure by damaging cellular DNA and protein, [19,20] thus leading to increased damage in the Eustachian tube and middle ear. In summary, the peroxidation of phospholipids in the cell membranes of the middle ear can prolong the duration of inflammation and thus lead to chronicity.…”
Section: Discussionmentioning
confidence: 99%
“…There is a minimal number of studies about oxidant and antioxidant mechanisms in patients with COM extant in the literature. [1,6,12,24] However, that a relationship between oxidative stress and COM exists is noteworthy.…”
Section: Discussionmentioning
confidence: 99%
“…A discharge lasting for more than three months is also present. [1] Even though it is accepted that COM is multifactorial in aetiology, the precise pathogenic mechanism has yet to be fully elucidated. [2][3][4] Numerous aetiological factors, including genetics, eustachian tube dysfunction, autoimmunity, infection, osteoclastic activity, cytokine profile alterations, the presence of endotoxins, and products of lipid peroxidation resulting from oxidative stress, have been proposed to explain the chronic inflammation which lies at the heart of the disorder.…”
Section: Introductionmentioning
confidence: 99%